Three-dimensional Differentiated Human Mesenchymal Stem Cells Exhibit Robust Antifibrotic Potential and Ameliorates Mouse Liver Fibrosis. (3rd February 2021) - Choi, Ja Sung; Park, Young-Jin; Kim, Sung-Whan
Recently, three-dimensional (3D)-cultured adipose mesenchymal stem cells (ASCs) have provided an effective therapy for liver fibrosis. This study aimed to enhance the potential of human ASCs for antifibrosis or hepatocyte regeneration using a 3D culture system and investigate their therapeutic mechanism in experimental liver fibrosis. ASC-3Dc were generated in a 3D culture system and stimulated with four growth factors, namely epidermal growth factor, insulin-like growth factor (IGF)-1, fibroblast growth factor-2, and vascular endothelial growth factor-A. The expression levels of antifibrotic or hepatic regeneration factors were then measured using quantitative real-time polymerase chain reaction and enzyme-linked immunosorbent assay. The therapeutic effects of ASC-3Dc were determined using a liver fibrosis model induced by thioacetamide. Histological analysis was performed to elucidate the therapeutic mechanism. ASC-3Dc exhibited high levels of hepatocyte growth factor (HGF), IGF-1, stromal cell-derived factor (SDF)-1 genes, and protein expression. In addition, injecting ASC-3Dc significantly prevented hepatic fibrosis and improved liver function in vivo. Moreover, high numbers of ki-67-expressing hepatocytes were detected in the ASC-3Dc-injected livers. Albumin-expressing ASC-3Dc engrafted in fibrotic livers augmented HGF expression. Thus, short-term 3D-cultured ASCs may be a novel alternative to the conventional treatment for liver damage in clinical settings.